A comparative study of the awareness and usage of prenatal and postnatal fluoride by mothers between two communities - Cruz, Marite R.; Rivera, Merceditas P.; Caparas, Lourdes P. (Adviser).
This paper aims to find out not only the difference in the awareness and usage of prenatal and postnatal fluoride between two communities but also the relationship between knowledge and usage. To this a survey was conducted in two typical communities in Metro Manila with contrasting socio-economic backgrounds. Subjects for the study include mothers with children fourteen years of age and below living in Community A, Krus na Ligas, and Community B, Kalaw Homes.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Fluorides; Dental caries -- Prevention